Medical image processing : (Esditions de I'Escole polytechnique de montréal, 1997)
This book introduce low-level image processing - an information theory stand point. Application of regularzatin methods to cardio-Vascular imaging. Modeling and optimization in bayesian tomographic reconstrution...